Exploring barriers to the agroecological transition in Nicaragua: A Technological Innovation Systems Approach - Schiller, Katharina J.F.; Klerkx, Laurens; Poortvliet, P. Marijn; Godek, Wendy (Informa UK Limited, 2019)
Latin America has historically been a vanguard of agroecology. In Nicaragua, an agroecological transition is occurring, with three decades of building a groundswell based on the farmer-to-farmer movement and the recent institutionalization of agroecology in national law. Yet, problems remain with agroecology’s diffusion. We introduce the Technological Innovation Systems approach to examine systemic barriers to the agroecological transition and cycles of blockages caused by barriers’ interactions. Based on qualitative data from north-central Nicaragua, we find the main barriers hindering the agroecological transition include weak guidance of the search for agroecology, insufficient capacities and quantities of resources, and lacking market development. Beyond the Nicaragua case, the analysis points at the importance of using socio-technical systems analysis to better understand and address the root causes behind issues blocking national agroecological transitions.